Atrial fibrillation and the risk of sudden cardiac arrest in patients with hypertrophic cardiomyopathy - A nationwide cohort study. (April 2021) - Liao, Min-Tsun; Wu, Cho-Kai; Juang, Jyh-Ming Jimmy; Lin, Ting-Tse; Wu, Chih-Cheng; Lin, Lian-Yu
Abstract: Background: Hypertrophic cardiomyopathy (HCM), affecting 0.2% of the population, is the leading cause of sudden cardiac arrest (SCA). Incident atrial fibrillation (AF) is associated with an increased risk of SCA in general population. To determine whether AF is associated with an increased risk of SCA in patients with HCM. Methods: This nationwide cohort study analyzed data from Registry for Catastrophic Illness, which encompassed almost 100% of the patients with HCM in Taiwan from 1996 to 2013. Follow-up and data analysis ended December 31, 2013. The main outcome was physician-adjudicated SCA, defined as death from a sudden, pulseless condition presumed due to a ventricular tachyarrhythmia. The secondary outcome was non-sudden cardiac death (NSCD), which was heart failure death, stroke death and non-HCM related death. We used Cox proportional hazards models to assess the association between AF and SCA/NSCD, adjusting for baseline demographic and cardiovascular risk factors. Findings: A total 10, 910 subjects participated in this study with mean age of 62 years. Among enrolled subjects, 1, 169 (10.7%) developed AF, which was independently associated with elder age, female sex, and history of heart failure (HF) hospitalization. During follow-up (median, 8.5 years and 2th to 7th interquartile range, 3.6 to 16.5 years), 371 SCA (166 in AF and 205 in non-AF group) and 797 NSCD (417 in AF and 380 in non-AF group) events occurred. The crude incidence rates of SCA were 12.45/1000 person-years (with AF) and 3.57/1000 person-years (without AF). The crude incidence rates for NSCD were 31.29/1000 person-years (with AF) and 6.63/1000 person-years (without AF). The multivariable hazard ratios (HRs) (95% CI) of AF for SCA and NSCD were 3.633 (2.756–4.791) and 2.086 (1.799–2.418), respectively. Furthermore, among the etiologies of NSCD, subjects with AF was at most risk of stroke-related death (HR, 6.609; 95% CI, 3.794–9.725). Interpretation: Incident AF is associated with an increased risk of SCA and NSCD in the HCM population. Early detection of AF may provide more comprehensive risk stratification of SCD in HCM population. Because of underuse of oral anticoagulants and the absence of primary prevention ICD therapy in our cohort, the application of our findings was limited for the general HCM population in the current clinical practice. Funding: None